TINDAK TUTUR PADA BERITA ACARA PEMERIKSAAN SEBAGAI PENEGAKAN HUKUM YANG SETARA DAN BERKEADILAN (KAJIAN LINGUISTIK FORENSIK) - Miftahul Jannah, Jamilah; Munirah, Munirah; Munir, Abdul (Jurnal Riset Guru Indonesia, 2024)
Forensics (derived from the Latin "forensis" which means "from outside", and is related to the word forum which means "public place") is a field of science that is used to assist the process of upholding justice through the process of applying knowledge or science. This Forensic Linguistics research focuses on the analysis of written text in the investigation report (hereinafter referred to as BAP) of investigators at the North Mamuju Pasangkayu Resort Police. The BAP is initial information regarding what the investigative team is investigating regarding allegations of criminal acts committed by the suspect. This process is stated to be important to explore what legal violations the suspect has committed, develop investigations, and determine the suspect's temporary status for criminal violations so that the articles determined are appropriate. This research aims to investigate (1) the use of commissive, directive and verdictive speech acts in preparing the structure of the BAP text (2) criminal facts arranged in the BAP text, and (3) the process of determining terms in legal language proposed by the police. The BAP data source was obtained from the North Mamuju Pasangkayu Resort police documentation which focuses on criminal acts in the field of fraud and/or embezzlement. The investigator's speech data was analyzed using forensic linguistic approaches with a pragmatic scalpel in three studies, namely speech acts, method of delivery, pragmatic power. The results of initial observational research show (1) the communication strategies used by investigators in investigating cases are commissive, directive and verdictive speech acts, using direct-literal delivery. Statements that are built from pragmatic power are statements of quantity, statements of quality, statements of method, and statements of relevance, (2) the criminal facts that occurred, namely fraud and/or embezzlement of funds for the purchase of land (plantation location) by Murtang alias Father Winda Bin Sannung biodata is available in the BAP, sale of location to Company PT. Palma is Haris' brother. In a position where there was embezzlement by the suspect of funds paid to the public. The two language facts alleged against the suspect are appropriate, but lacking. This research is expected to make a theoretical contribution to the development of forensic linguistic studies, especially in the use of pragmatics as an analysis that focuses on speech acts or language acts. It is hoped that this research can contribute to a more in-depth investigation of language facts that emerge from both the investigator and the examinee.